(untitled) (Research, Society and Development, 2022)
Cervical cancer is the third type of malignant neoplasm that most causes the death of women in Brazil. Associated with the HPV virus, it can evolve aggressively over a period of up to 20 years. For this reason, it is important to raise awareness about the importance of preventive exams offered by Primary Health Care. In this context, this essay is justified by the need to discuss the functionality of essential health services as fundamental in the early detection of cancerous pathologies, often found through cytological examinations in asymptomatic people. The objective was to describe the ABS strategies aimed at the diagnosis and treatment of cervical cancer in Brazil, as well as to present the statistical results of death from this disease between the years 2017 and 2019, to reflect on the effectiveness of public policies in health aimed at combating the disease and analyze, based on statistical records, its regressive trend. Methodologically, a narrative review of the literature was carried out based on scientific articles, theses, dissertations and institutional information from the Ministry of Health and the National Cancer Institute, published in Cadernos de Atenção Básica and on digital platforms. As a result, there is the repercussion of the actions developed by the ABS to combat cervical cancer, as well as the deficiency and fragility of the service, based on the death records released by the Ministry of Health in the three-year period from 2017 to 2019 and, also, conclusions about the regressive trend in the number of deaths.